Word Formation Process of Slang Word Used by Gamers In The Game Online “Mobile Legend” - Vera Magria; Asridayani Asridayani; Rosa Winda Sari (Jurnal Ilmiah Langue and Parole, 2021)
This research analyzes about word formation process of slang word used by gamers in the game online “Mobile Legend”. The purposes of this research are to classify and to analyze the types of word formation processes of slang words used by gamers using theory word formation process by Yule (2010) and Katamba (2005) and to describe the meaning of slang words used by gamers. The method used in this research is descriptive qualitative. The data is formed of slang word in chat feature by gamers. In collecting the data, the researcher used participant observational method (SLC). Then, the analysis in this research, the researcher used agih method (distributional method) and used Segmenting Immediate Constituents Techniques (Teknik Bagi Unsur langsung/BUL) as the basic technique and delition technique (teknik lesap) as an advanced technique. The results of this research are stated as follows. Firstly, six types of word formation process in slang word used by gamers; abbreviation, acronym, borrowing, compounding, multiple process, and clipping. Then, the researcher found twelve slang words that utterances by gamer. While for word formation process, the type that dominant is compounding. In the meaning of slang word, the researcher only finds two from seven types of meaning by Leech (1981), they are: firstly social meaning and secondly connotative meaning.